Wstępna ocena monitoringu opadów atmosferycznych i sygnalizacji wystapienia odpływów burzowych na terenie miasta Głogów = Preliminary assessment of monitoring of atmospheric recipitation and storm overflow signalling in the city Głogów - Nowogoński, Ireneusz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The paper presents preliminary results of precipitation monitoring network in the city Głogów. Rainfall variability in time for the phenomena of the most rainfall intensities during research period was presented. Contrasted the results with measurements of sewage levels above the overflows weirs of three overflow structures located in the analyzed system.
Keywords: kanalizacja ogólnospławna; monitoring; combined sewer systems